THE MAIN FACTORS OF ECONOMIC AND ENERGY EFFICIENCY OF MINING TRANSPORTATION MACHINES IN MINERAL EXTRACTION TECHNOLOGIES: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The increase in production capacity, depth of development and technological load flows, transportation distances and slopes of routes, as well as the need to reduce operating and energy costs of mining directly determine the main directions for the improvement and development of open-pit transportation systems and increase the operational performance, as well as individual types of mining transport machines used in mining operations.